Perlindungan terhadap Perempuan Adat: Kritik Hukum Feminis terhadap Penegakan CEDAW dalam Kasus Kawin Tangkap di Sumba Tengah - Sherly Aprilia; Arief Setiawan (Jurnal HAM, 2026)
This article is based on research examining the implementation of CEDAW in Indonesia in overcoming the practice of kawin tangkap as discrimination against women in Central Sumba. The research aims to analyze the implementation of CEDAW in Central Sumba, particularly in the aspect of law enforcement regarding cases of kawin tangkap. It examines why the implementation of CEDAW has not been effective in overcoming gender-based violence manifested in kawin tangkap practices in Central Sumba. Qualitative explanative research design was employed, utilizing case study approach in 2014-2025. The research involved participatory observation in Central Sumba. Data were collected through interviews with survivors, activists of NGOs, government, law enforcement officers, and literature review. Despite Indonesia’s ratification of CEDAW in 1984, cases of kawin tangkap continue to persist. The ratification has not yielded significant impacts, especially in terms of law enforcement, as evidenced in the absence of any officially reported cases that are successfully prosecuted. Feminist legal theory is applied to critically examine the limitations of CEDAW as a framework of positive law in ensuring the effective protection and respect of women’s rights through law enforcement mechanisms. By integrating the concept of intersectionality and Johan Galtung’s theory of violence, this analysis shows how overlapping social identities can perpetuate—especially those shaped by cultural and structural factors—can produce conditions that justify violation practices of kawin tangkap. The researcher suggests the need for alignment in understanding kawin tangkap as a form of discrimination and violence against women by all parties, accompanied by consistent and impartial law enforcement.